Performance Improvement through Local Planning: Action Research - Yousuf Hasan, M and Rushikesh M. Maru (Journal of Health Management 1(1) 1999, 1999)
Local level performance review, planning and monitoring can increase the productivity of the family planning programme. How such a management process can be institutionalised in a government programme setting was a key research question of a quasi-experimental design intervention. An organisational diagnosis was conducted, followed by feedback and training workshops designed to orient programme managers in performance assessment, planning, problem-solving techniques, leadership and supervisory styles. This intervention was tested in high and low performing areas. The paper describes the conceptual framework and implementation methodology of performance review and planning, and then discusses the results in terms of performance output and activities.